Cough and fear of sleep: early clinical signs of Bordetella pertussis in an adult - Jones,Thomas C. (2004)
Pertussis is increasing in frequency among adults, but early diagnosis requires special attention to details in the medical history. We describe a 64 year-old male with classic signs and symptoms of pertussis and documented Bordetella pertussis infection that were overlooked because he presented with a chief complaint of cough and fear of falling asleep. Coughing paroxysms and a feeling of suffocation (30-60 seconds) only occurred at night after short periods of deep sleep (30-45 minutes). The physicians did not observe these episodes during daytime examinations, and the basis of the patient's fear of sleep was not explored. We recommend reassessment of how adults describe symptoms of pertussis, including fear of sleep, and we suggest the use of PCR technology to allow early diagnosis and prompt treatment.